Training Discipline of Students in The Manakib Reading Tradition at Nurul Qur'an Pakunden Islamic Boarding School Ponorogo - Muhammad Nurzakka (Jurnal Living Hadis, 2022)
This research is a descriptive-qualitative study that discusses the practice and tradition of reading the manakib of Sheikh Abdul Qadir al-Jilani which is carried out every selapanan (thirty-five days in the Javanese calendar), more precisely every Kliwon Friday night at the Nurul Qur'an Pakunden Islamic Boarding School in Ponorogo. The living hadith approach is used to find receptions for the students related to the normative text that underlies these activities, with interview techniques as a data collection method. This research focuses on the study of how the practice of implementing activities, what factors influence the practice, and how these practices can affect the diversity of the students. The conclusions of this study are: 1) the practice of reading manakib in the Nurul Qur'an Islamic boarding school is a religious tradition that has been implemented for a long time, which is about thirty years since the boarding school was founded, although in the course of the pesantren program, this activity had experienced a vacuum due to the change of management which had an impact on the absence of a special program as a forum for this activity. 2) there are two hadiths as the normative basis for the implementation of the tradition. 3) the tradition of reading the manakib is a forum and means for the caregivers and administrators to instill discipline in the students in the hope that they can preserve the tradition when they are struggling in their respective areas